NMR‐based metabolomic approach for EVOO from secular olive trees of Apulia region. Issue 9 (5th August 2013) - Del Coco, Laura; Perri, Enzo; Cesari, Gianluigi; Muzzalupo, Innocenzo; Zelasco, Samanta; Simeone, Vito; Schena, Francesco Paolo; Fanizzi, Francesco Paolo
<x xml:space="preserve">Abstract</x> In this work, a first level investigation was carried out to study the extra virgin olive oils (EVOOs) obtained from secular olive trees of Apulia region. Microextracted olive oil samples from selected and genetically characterized olive trees were studied by 1H NMR‐based metabolomic approach and multivariate analysis, according to cultivar and geographic origin, within the Apulia region. The 1H NMR spectra of oils were analyzed by several pattern recognition methods, using both unsupervised (principal component analysis) and supervised (partial least squares discriminant analysis, orthogonal partial least squares discriminant analysis (OPLS‐DA)) statistical techniques. EVOOs obtained from secular olive trees could be easily differentiated by OPLS‐DA not only depending on the used cultivars but also according to their geographical origin within the different districts of the Apulia region, such to justify a larger biodiversity maintenance of Apulia secular germplasm. Therefore, differences in chemical composition and NMR profiles of EVOOs may be explained either by cultivars or geographic areas. Practical applications: About 10% of the genetic olive tree patrimony within the Apulia region consists of the secular olive trees. A recently introduced regional law (No 14 of June 4th, 2007) allows to exploit oil produced from secular olive trees by labeling it with the special mention: "extra virgin oil from the Apulia secular olive trees". Characterization of extra virgin olive oils obtained from secular trees may be an optimal solution to increase the value for this product and make it available on the market. On the other hand this economic issue is very important to preserve the unique landscape offered by the ancient olive groves of the Apulia region in south east Italy.